The RISE Framework - Balseca, Esteban; Cuesta, Jose Antonio; Damania, Richard; Feng, Shenghui; Moon, Jisung; Rentschler, Jun; Russ, Jason; Triyana, Margaret (World Bank, Washington, DC, 2022)
The world has witnessed unparalleled economic progress in the last three decades. But success is not preordained, and several headwinds threaten this hard fought progress. Inequality is leaving many people and subgroups behind and excluding them from enjoying the benefits of this great economic expansion. More recently, the world has awakened to the reality of a new type of risk. The coronavirus disease 2019 (COVID-19) struck at a time when the world was healthier and wealthier than ever before. There is little disagreement over the need to enable a recovery that is fairer, safer, and more sustainable. This report describes how these ambitious objectives can be achieved by providing evidence based tools and information to guide countries to spend better and improve policies. It is in this context that this document presents policy guidance to identify and diagnose key development challenges and develop solutions to help countries build better.